ANALISIS BAURAN PEMASARAN PADA DEALER ASTRA MOTOR DI KOTA BIMA - Indah Fitriyani; Sri Ernawati (University of Riau Kepulauan, 2021)
The purpose of this research is to identify and analyze the problem of the marketing mix at Astra Motor Dealers in Bima City. The type of research in this research is descriptive research. This research was conducted at Astra Motor Dealers in Bima City. The population in this study is all consumers who have bought a motorcycle at an Astra Motor Dealer in Bima City whose number is unknown (unknown population). The sampling technique used in this study was purposive sampling and obtained a sample of 100 respondents. Collecting data using literature study, observation and questionnaires. The data analysis technique used in this research is validity test, reliability test and statistical analysis. The results of this study indicate that the marketing mix at Astra Motor Dealers in Bima City is more than 70% of the expected good.